2022
DOI: 10.1111/ans.17808
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine associated cervical lymphadenopathy: a case series

Abstract: Background COVID‐19 is an evolving worldwide pandemic causing significant morbidity and mortality. COVID‐19 vaccinations have been developed to increase immunity against the virus. In New Zealand, the Pfizer BioNTech mRNA vaccine has been provisionally approved for use. Axillary lymphadenopathy is a recognized side effect of the mRNA vaccine, however cervical lymphadenopathy has also been reported. Due to a wide range of differential diagnoses, the finding of cervical lymphadenopathy requires thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Reactive change was most frequently reported. A total of 36 studies including one single-center retrospective study [ 45 ], five case series [ 19 , 46 , 47 , 48 , 49 ] and 30 case reports [ 8 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] revealed that C19-VAL is due to a reactive change in LN. It is an immune response for other vaccines [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reactive change was most frequently reported. A total of 36 studies including one single-center retrospective study [ 45 ], five case series [ 19 , 46 , 47 , 48 , 49 ] and 30 case reports [ 8 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] revealed that C19-VAL is due to a reactive change in LN. It is an immune response for other vaccines [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…
We would like to correspond on the publication 'COVID-19 vaccine associated cervical lymphadenopathy: a case series'. 1 With increasing levels of COVID-19 immunization and booster vaccinations, Heaven et al predicted that cases of COVID-19 vaccine-associated cervical lymphadenopathy would continue to emerge. 1 The necessity of obtaining a COVID-19 immunization history and adding COVID-19 linked cervical lymphadenopathy in the differential diagnosis of a neck lump was noted by Heaven et al 1 We agree that people who received the vaccine could suffer unanticipated cervical lymphadenopathy.
…”
mentioning
confidence: 99%
“…We would like to correspond on the publication ‘COVID‐19 vaccine associated cervical lymphadenopathy: a case series’. 1 With increasing levels of COVID‐19 immunization and booster vaccinations, Heaven et al . predicted that cases of COVID‐19 vaccine‐associated cervical lymphadenopathy would continue to emerge.…”
mentioning
confidence: 99%
See 2 more Smart Citations